2021
DOI: 10.1108/jtf-11-2020-0194
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach for predicting loyalty behavior of tourist destinations

Abstract: PurposeDestinations to be able to compete with each other need to equip themselves with as many competitive advantages as possible. Tourists' loyalty to a destination is considered as a prominent competitive tool for destinations. Tourists' loyalty manifests itself in recommendation of the destination to others, repeat visit of the destination and willingness to revisit the destination. Although a plethora of studies have tried to define models to show the relation between loyalty and the antecedent factors le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Ayrıca, destinasyonu yakınlarına, çevresine tavsiye etmekte, gelecekteki ziyaretlerinde ilk tercihleri olmaktadır. Bu da destinasyon için rekabet avantajı oluşturmaktadır (Malmiri, Isfahani, Toroody ve Abaei, 2021). Bu sebeple, çok sayıda turistik çekim unsuruna sahip Burhaniye destinasyonunu ziyaret eden turistlerin sadakat eğilimlerinin yüksek olması, iç turizm açısından destinasyonun rekabet gücünü artırmada önemli bir stratejik araç olarak düşünülebilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Ayrıca, destinasyonu yakınlarına, çevresine tavsiye etmekte, gelecekteki ziyaretlerinde ilk tercihleri olmaktadır. Bu da destinasyon için rekabet avantajı oluşturmaktadır (Malmiri, Isfahani, Toroody ve Abaei, 2021). Bu sebeple, çok sayıda turistik çekim unsuruna sahip Burhaniye destinasyonunu ziyaret eden turistlerin sadakat eğilimlerinin yüksek olması, iç turizm açısından destinasyonun rekabet gücünü artırmada önemli bir stratejik araç olarak düşünülebilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Past studies have revealed that psychological variables, particularly destination image influence consumer behaviour before, during and after visiting a destination (Chen and Hsu, 2000). Talaee Malmiri et al . (2021) suggested that destination image is one of the most dominant factors that affect tourists' behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have revealed that psychological variables, particularly destination image influence consumer behaviour before, during and after visiting a destination (Chen and Hsu, 2000). Talaee Malmiri et al (2021) suggested that destination image is one of the most dominant factors that affect tourists' behaviour. Destination image is "the totality of impressions, beliefs, ideas, expectations and feelings accumulated towards a place over time" (Kim and Richardson, 2003, p. 128).…”
Section: Introductionmentioning
confidence: 99%